PENGARUH KEAMANAN, DISPLAY PRODUK, DAN NILAI PELANGGAN TERHADAP MINAT BELI PADA RAMAYANA DEPARTEMEN STORE - Heryenzus; Jackhon Pahala Simanjuntak; Yopi; Agus Defri Yando (Jurnal PROFITA : Akuntansi dan Manajemen, 2023)
This study aims to determine the effect of security, product display and customer value on purchase intention at Ramayana Department Store . Data was collected by distributing questionnaires via Google from. The research population is 100 customers at Ramayana Department Store. The technique used in this study is a non-probability sampling technique, namely purposive sampling technique. The data in this study were collected by questionnaire and analyzed using the SPSS version 25 program. The findings of the study were that security has a positive and partial effect on purchase intention with t count 3.261 > t table 1.98498 and a significance value of 0.000 t table 1.98498 and a significance value of 0.000 t table 1.98498 and a significance value of 0.000 f table of 2.47 and a significance value of 0.000 <0.05.